THE EFFECTIVENESS OF INSECTICIDE APPLICATION WITH ACTIVE INGREDIENT CYPERMETHRIN ON THE INTENSITY OF ATTACKS BY Oryctes rhinoceros L. ON OIL PALM PLANTS ( Elaeis guineensis Jacq.) HAS NOT YET PRODUCED RESULTS - Muhammad Dzikri Almahdi Hasibuan; Hilwa Walida; Badrul Ainy Dalimunthe; Siti Hartati Yusida Saragih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The rhinoceros beetle ( Oryctes rhinoceros L.) is one of the main pests in oil palm plants that can cause serious damage, especially in the Immature Plant (IMPACT) phase. This pest attack causes damage to the growing point, thus inhibiting vegetative growth, reducing plant vigor, and potentially delaying the plant entering the productive phase. One of the control efforts commonly applied in oil palm plantations is the use of insecticides containing the active ingredient cypermethrin. This study aims to evaluate the effectiveness of cypermethrin application in reducing the intensity of O. rhinoceros attacks on IMPACT phase oil palm plants at PTPN IV Regional 1 Rantauprapat Plantation. The study was conducted in January–February 2026 using a field observation method with a quantitative approach and a paired observation design . A total of 114 sample plants from Blocks N07, N09, and O07 were observed before and after cypermethrin application at a dose of 1.6 cc per plant. Data were analyzed descriptively and tested using a Paired Sample t-test at a significance level of 5%. The results showed that the average attack intensity decreased from 78.07% before application to 20.18% after application, with a control efficiency of 74.15%. The results of statistical tests showed that cypermethrin application had a significant effect on reducing the intensity of O. rhinoceros attacks ( p < 0.05). Thus, cypermethrin is effective as a control measure against active attacks of O. rhinoceros on oil palm plants in the TBM phase. However, its use still needs to be combined with the implementation of Integrated Pest Management (IPM) to increase control effectiveness and reduce the risk of insecticide resistance.